Child-Friendly School Environment in the Perspective of Constructivism Theory: An Exploration of Human Resources in Education - Iwan Hermawan; Inayah Inayah; Suharmanto Suharmanto; Luqman Khakim; Jati Nugroho; Nur Nelisa Adah (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
Child-friendly school education is education with a pleasant learning atmosphere and supports teachers’ ability to implement active, collaborative, and democratic learning in the context of edutainment. Child-friendly school education programs are considered capable of strengthening the character of children to become individuals with noble character. In 2020, Indonesia had 36,766 child-friendly schools spread across the country. However, the current implementation of child-friendly schools is still not optimal considering the many phenomena of bullying problems that are increasingly rampant. This is in line with the data that in Indonesia there were 12,285 children experiencing violence, and the data continued to increase in 2020 to 12,425 and 2022 as many as 15,972 children. This quantitative study included 138 teacher respondents. The obtained data were analyzed using a structural equation model with SmartPLS software. This research builds a model that involves the Variables Of Technology Knowledge And Teaching Aids as endogenous variables with Educational Competence as a mediating variable to improve Child-Friendly School Performance. The results revealed that the model built fit is proven that Educational Competence can leverage Teaching Aids and Technology Knowledge on Child-Friendly School Performance with the best path being Teaching Aids->Educational Competence-> Child-Friendly School Performance, with a total effect of 0.239198. This research contributes to the body of knowledge of Constructivism Theory.